Reading Mark in context: Jesus and Second Temple Judaism - Blackwell, Ben C.; Goodrich, John K.; Maston, Jason (HarperCollins Christian Publishing, 2018)
For several decades, the Jewishness of Jesus has been at the forefront of scholarship. Students of the New Testament are more than ever aware of the importance of understanding Jesus and the Gospels in their Jewish context. In Reading Mark in Context, a team of Gospel scholars explore the Gospel of Mark in light of Second Temple Jewish literature.